Risk evaluation in patients undergoing coronary angiographic and angioplastic procedures with radial access. (September 2016) - Vigna, Luca; Lizio, Domenico; Matheoud, Roberta; Cannillo, Barbara; Chiappino, Paolo; Brambilla, Marco
Abstract : Introduction: Nowadays interventional cardiac procedures are of concern for the relatively high doses delivered to patients. Purpose: To estimate the effective dose (E), the organ doses (Ht ) and the related risk for cancer induction in terms of radiation exposure-induced death (REID) in patients undergoing coronary angiography (CA) and percutaneous transluminal coronary angioplasty (PTCA) procedures with radial access. Materials and methods: 65 patients underwent CA and PTCA interventions on a Philips Allura XPer FD10 angiographic equipment. For each patient, Xray tube voltage, projection, filtration, field dimensions and DAP were obtained by filming the monitor of the workstation during the entire procedure. E and Ht were evaluated by means of the MonteCarlo code PCXMC that models radiation beam and transport in an anthropomorphic phantom, allowing also the evaluation of REID. Results: Mean fluoroscopy time, DAP and E were: 3.1 min, 29.9 Gyxcm 2, 9.1 mSv and 8.9 min, 60.9 Gyxcm 2, 20.3 mSv for CA and PTCA, respectively; the correlation with DAP was very good in CA (r = 0.99) and in PTCA (r = 0.93). For both CA and PTCA, the most irradiated organs were lungs, oesophagus and red marrow, whose mean Ht were 32.5 mSv, 30.7 mSv, 11.6 mSv for CA and 58.5 mSv, 66.7 mSv, 24.9 mSv for PTCA; the highest REIDs were for induction of leukemia (0.04% and 0.08%) and lung cancer (0.14% and 0.20%). Conclusions: Cardiac interventional procedures with radial access improves patient compliance, reduces haemorrhagic complications compared to femoral access with comparable E and Ht values.